Narratives to wear: Fashion and intermidiality on Margaret Atwood’s The Handmade’s Tale (ModaPalavra e-periódico, 2024)
Presented here is the union of literature and fashion as media in the construction of social meaning, from The Handmaid’s Tale (ATWOOD, 2017) adapted to Vaquera’s fashion show, connected to the TV show. The objective is to evaluate the intermedia relations between the narrative construction and the runway clothes, associating the criticality of the literary work to the adaptation, sewn into molds and fabrics. It was resorted to Calanca (2011), Clüver (2012), Chevalier and Gheerbrandt (2001), Heller (2013), Moser (2006), Rajewsky (2005), among others: the intermedia propels the relations between fashion and literature as social constructs. Analyzing the clothing’s verb-visual elements - from literature to runway, tied into the series -, it has been observed that runway attires (re)construct Atwood’s narrative criticism, traversing to the garments’ colors, fabrics, and modelings that argue historically produced concepts regarding genders and social roles, problematizing the muzzling imposed to women since its literary narrative.